Caribbean Report 20-06-1990 - Whitehorne, Pat (anchor); Williams, Eddie (correspondent); Gunness, Chris (correspondent); Paquin, Lionel (interviewee); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1990)
The national army of Suriname takes control of the bauxite town of Moengo from the Jungle Commando rebels. Before fleeing the town, the rebels shot at army soldiers and blew up the head office of the Suriname Aluminium Company (SURALCO). Secondly, the Dutch government pressures St. Maarten delegates not to attend the Caribbean regional seminar on decolonization. Following the Financial News, a representative of the United Nations Secretary General on Haiti left New York for consultation with the government of Haiti in Port-au-Prince. The representative was appointed to determine how the United Nations can assist in the organization of Haiti’s upcoming elections. In addition, the National Front for Change and Democracy is a new political organization formed in Haiti. The new party comprises of fifteen left-wing organizations coming together to participate in the forthcoming elections in Haiti.
1. Headlines (00:00-00:35)
2. The National Army of Suriname regains control of the bauxite town of Moengo. Pat Whitehorne interviews an army spokesman (00:36-05:12)
3. The Dutch government forces St. Maarteen out of the Decolonization Seminar in Barbados. Eddie Williams reports from Barbados (05:13-07:24)
4. Financial News (07:25-08:13)
Keywords: Insurgency - Suriname.; Decolonization -- Saint Maarten -- Congresses.; Elections -- Haiti.; Election monitoring -- Haiti -- United Nations.; Political parties -- Haiti.; Haiti -- Politics and government.; Jungle Commando -- Suriname.; National Front for Change and Democracy -- Haiti.